Molecular and Photosynthetic Performance in the Yellow Leaf Mutant of Torreya grandis According to Transcriptome Sequencing, Chlorophyll a Fluorescence, and Modulated 820 nm Reflection - Jianshuang Shen; Xueqin Li; Xiangtao Zhu; Zhicheng Ding; Xiaoling Huang; Xia Chen; Songheng Jin (Cells, 2022)
To study the photosynthetic energy mechanism and electron transfer in yellow leaves, transcriptomics combined with physiological approaches was used to explore the mechanism of the yellow leaf mutant Torreya grandis ‘Merrillii’. The results showed that chlorophyll content, the maximal photochemical efficiency of PSII (Fv/Fm), and the parameters related to the OJ phase of fluorescence (φEo, φRo) were all decreased significantly in mutant-type T. grandis leaves. The efficiency needed for an electron to be transferred from the reduced carriers between the two photosystems to the end acceptors of the PSI (δRo) and the quantum yield of the energy dissipation (φDo) were higher in the leaves of mutant-type T. grandis compared to those in wild-type leaves. Analysis of the prompt fluorescence kinetics and modulated 820 nm reflection showed that the electron transfer of PSII was decreased, and PSI activity was increased in yellow T. grandis leaves. Transcriptome data showed that the unigenes involved in chlorophyll synthesis and the photosynthetic electron transport complex were downregulated in the leaves of mutant-type T. grandis compared to wild-type leaves, while there were no observable changes in carotenoid content and biosynthesis. These findings suggest that the downregulation of genes involved in chlorophyll synthesis leads to decreased chlorophyll content, resulting in both PSI activity and carotenoids having higher tolerance when acting as photo-protective mechanisms for coping with chlorophyll deficit and decrease in linear electron transport in PSII.